HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN DIIT PADA LANSIA HIPERTENSI - Lestari, Ratna (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2024)
Background: Hypertension is a condition of a person's blood pressure is higher than 140 mmHg for systolic and 90 mmHg for diastolic. One of the strategies to manage hypertension is an adequate diet. However, the level of obedience on the hypertension diet is influenced by the level of knowledge. Purpose: This study aimed to determine the correlation between the level of knowledge with hypertension dietary compliance in elderly at Puskesmas Kalasan Area. Methods: This study used cross sectional design with proportional random sampling. This study involved 93 elderly with hypertension as respondents. The level of knowledge and compliance are collected by adopted questionnaire, while the statistical test used is Gamma Somer's D. Result: The result shows p-value 0.000 (<0.05) and the correlation coefficient r 0.815 in a positive direction. Conclusion: These means that there is correlation between knowledge and behavior compliance of hypertension diet. Elderly need accomplishment from family and health worker through education or other action in order to stay healthy with hypertension.Keywords : Knowledge, Compliance, Hypertension Diet, Elderly